Talking heads : the neuroscience of language - Denes, G. (Psychology Press, 2011)
"The origin, development, and nature of language has been the focus of theoretical debate among philosophers for many centuries. Following the discovery 150 years ago that language is a biological system, an increasing number of neuroscientists began to search for its anatomical basis and its links with other such systems. The relatively recent introduction of neuroimaging tools, such as PET and MRI, has brought rapid and groundbreaking developments to the field of Neurolinguistics. In this book, Denes and Smith harness these advances to adopt a biolinguistic approach to the study of a subject that increasingly sees the collaboration of linguists, experimental psychologists, neuroscientists and clinicians. Following an up-to-date description of acquired language disorders, and their contribution to the design of a functional architecture of language, the book illustrates the neurological process involved in the production of written language, as well as investigating the neurological systems responsible for sign language production and second language acquisition. Talking Heads reviews the latest research on the nature, structure and origin of language to provide a concise analysis of the multifaceted aspects of language which focuses both on theoretical aspects and physical implementation. With a glossary of the anatomical and linguistic terms, this book provides an invaluable resource to undergraduate and graduate students of Psychology, Psycholinguistics and Linguistics. It will also be of interest to neurologists, speech therapists and anyone interested in the mind-brain problem"--Provided by publisher.